Posterior circulation aneurysms: A 10-year institutional analysis - Saurabh Sharma; P. Sarat Chandra; Ansari Abuzer; Ashish Suri; Shailesh Gaikwad; N.K. Mishra; H.H. Dash; B.S. Sharma; A.K. Mahapatra (Indian Journal of Neurosurgery)
Background Aneurysms are uncommon and challenging to manage.